2015
DOI: 10.1016/j.engstruct.2015.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic amplification of a multi-span, continuous orthotropic bridge deck under vehicular movement

Abstract: __________________________________________________________________________The response of a multi-span, continuous orthotropic bridge deck during truck loading is investigated to better understand the dynamic interaction between moving vehicles and highway bridge decks. The present study is based on a recently published, semi-analytical approach for free vibration in which the modal superposition method incorporates intermodal coupling. Herein, the bridge deck is modeled as a jointless, multi-span, orthotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In a recent publication, ref. [13] report on DAF results for sagging bending moment in continuous bridges; however, there is no mention to hogging moments. The modes of vibration of a structure are characterized by their mode shape and their modal frequency.…”
Section: Daf =mentioning
confidence: 99%
“…In a recent publication, ref. [13] report on DAF results for sagging bending moment in continuous bridges; however, there is no mention to hogging moments. The modes of vibration of a structure are characterized by their mode shape and their modal frequency.…”
Section: Daf =mentioning
confidence: 99%
“…The equations of fitted lines can be obtained as Eqs. (6) and (7). The DAF is a function of / in these equations.…”
Section: Dynamic Amplification Factor Calculatementioning
confidence: 99%
“…In their analysis, it was found that torsion modes due to curvature of the deck considerably influence the DAF. Rezaiguia [7] found that when the load is applied far from the central axis of the deck, the impact factor (IF) obtains in the considerable presence of torsion modes.…”
Section: Introductionmentioning
confidence: 99%
“…The total response has both static and dynamic components. Dynamic Amplification Factor (DAF) is a term widely used in the literature Mohammed, Cantero, González, & Al-Sabah, 2014;Rezaiguia, Ouelaa, Laefer, & Guenfoud, 2015) to quantify the interaction between the bridge and vehicle. Dynamic Amplification Factor is defined as the ratio of the maximum total response to the maximum static response during a vehicle crossing, for the load effect of the bridge being examined (i.e., bending moment at mid-span section).…”
Section: Introductionmentioning
confidence: 99%